How to Manage Pouchitis in Ulcerative Colitis? - Magro, F.; Lopes, S.; Rodrigues, S.; Azevedo, I. (Current Drug Targets, 2011)
It is estimated that 50% of patients who have undergone ileal pouch-anal anastomosis (IPAA) surgery for UC will develop at least one episode of pouchitis. The risk of developing pouchitis is much higher in patients with preoperative extraintestinal manifestations and primary sclerosing cholangitis. In acute pouchtis metronidazole or ciprofloxacin have shown efficacy, however there is some evidence that ciprofloxacin may have better and has less toxic. In patients with chronic pouchitis antibiotics are less effective, and maintenance therapy may be required. In cases of refractoriness to conventional therapy a combination of two antibiotics for a prolonged period or infliximab may be effective. Starting maintenance treatment with highly concentrated probiotics is recommended as primary and secondary prophylaxis.
Keywords: Probiotics